Pengembangan Media Pembelajaran SIPANCA Berbasis Game Interaktif pada Materi Makna Sila-Sila Pancasila untuk Siswa Kelas III Sekolah Dasar - Achime Rahma Arswendya; Jatmiko; Aan Nurfahrudianto (Lembaga Yasin AlSys, 2026)
The low level of understanding among third-grade students at SDN Lirboyo 2 regarding the meanings of the Pancasila principles was indicated by 73.07% of students who had not achieved the Learning Objective Achievement Criteria (KKTP), accompanied by limited learning media that still consisted of images and simple PowerPoint slides. This study aimed to develop SiPanca (Sila-Sila Pancasila) learning media based on an interactive game and analyze its validity, practicality, and effectiveness for third-grade students at SDN Lirboyo 2. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the analysis, design, development, implementation, and evaluation stages. The research participants consisted of one classroom teacher and 26 third-grade students. Data were collected through observation, interviews, questionnaires, and pretest–posttest assessments using expert validation sheets, teacher and student response questionnaires, and test questions as the research instruments. The results showed that the SiPanca media obtained an average validation score of 95% from the subject matter and media experts, placing it in the highly valid category. The practicality of the media based on the teacher’s response reached 90.91%, while the students’ responses in the large-scale trial reached 94.5%, both of which were classified as highly practical. The effectiveness of the media was demonstrated by an increase in the students’ mean score from 50.8 to 88.4 and an increase in classical mastery from 10% to 90%, placing it in the highly effective category. These findings confirm that the SiPanca interactive game-based learning media is valid, practical, and effective as an alternative learning medium for Pancasila Education on the meanings of the Pancasila principles in elementary schools. In practical terms, the SiPanca media can assist teachers in delivering more concrete, interactive, and enjoyable learning and serve as a reference for developing similar media for other Pancasila Education materials.